Hydrological Extremes in a Warming Climate Nonstationarity, Uncertainties and Impacts - Shrestha, Rajesh R.; Najafi, Mohammad Reza (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue comprises 11 papers that outline the advances in research on various aspects of climate change impacts on hydrologic extremes, including both drivers (temperature, precipitation, and snow) and effects (peak flow, low flow, and water temperature). These studies cover a broad range of topics on hydrological extremes, including hydro-climatic controls, trends, homogeneity, nonstationarity, compound events and associated uncertainties, for both historical and future climates.